Cross-national differences in risk preference and individual deprivation: A large-scale empirical study. (1st May 2018) - Canale, Natale; Vieno, Alessio; Lenzi, Michela; Griffiths, Mark D.; Perkins, Douglas D.; Santinello, Massimo
Abstract: Although risk-taking has been found to be associated with economic deprivation, there is little evidence on whether the relationship between individual deprivation and propensity for risk-taking is inherent to all individuals, or varies across cultural contexts. Consequently, the present study investigated the interaction effects of macroeconomic factors [Gross Domestic Product (GDP) per capita and Human Development Index (HDI)] in the relationship between individual deprivation and propensity for risk-taking using the World Values Survey data from 58 countries ( N  = 87, 223). On average, individuals in more developed countries (higher HDI) had less propensity for risk-taking. However, in contradiction to this, the positive association between individual deprivation and risk-taking was stronger in countries with higher GDP per capita. The present study suggests that the association between individual deprivation and propensity for risk-taking varies with environmental variables assessing the socio-economic development of a country. Highlights: Propensity for risk-taking (PRT) is associated with individual deprivation (ID). People in more developed countries had less PRT. In contradiction to this, the ID-PRT association is stronger in richer countries.